FtsZ of Filamentous, Heterocyst-Forming Cyanobacteria Has a Conserved N-Terminal Peptide Required for Normal FtsZ Polymerization and Cell Division - Corrales-Guerrero, Laura; Camargo, Sergio; Valladares, Ana; Picossi, Silvia; Luque, Ignacio; Ochoa de Alda, Jesús A. G.; Herrero, Antonia (Frontiers in Microbiology, 2018)
Filamentous cyanobacteria grow by intercalary cell division, which should involve distinct steps compared to those producing separate daughter cells. The N-terminal region of FtsZ is highly conserved in the clade of filamentous cyanobacteria capable of cell differentiation. A derivative of the model strain Anabaena sp. PCC 7120 expressing only an FtsZ lacking the amino acids 2-51 of the N-terminal peptide (N-FtsZ) could not be segregated. Strain CSL110 expresses both N-FtsZ, from the endogenous ftsZ gene promoter, and the native FtsZ from a synthetic regulated promoter. Under conditions of N-FtsZ predominance, cells of strain CSL110 progressively enlarge, reflecting reduced cell division, and show instances of asymmetric cell division and aberrant Z-structures notably differing from the Z-ring formed by FtsZ in the wild type. In bacterial 2-hybrid assays FtsZ interacted withN-FtsZ. However, N-FtsZ-GFP appeared impaired for incorporation into Z-rings when expressed together with FtsZ. FtsZ, but not N-FtsZ, interacted with the essential protein SepF. Both FtsZ and N-FtsZ polymerize in vitro exhibiting comparable GTPase activities. However, filaments of FtsZ show a distinct curling forming toroids, whereas N-FtsZ form thick bundles of straight filaments. Thus, the N-terminal FtsZ sequence appears to contribute to a distinct FtsZ polymerization mode that is essential for cell division and division plane location in Anabaena.